(untitled) (Jurnal Teknologi Industri Pertanian, 2024)
Oil Palm Empty Fruit Bunch (OPEFB) is biomass by-products from palm oil processing mills. The cellulose content in OPEFB, which reaches 38.70%, presents a potential raw material for various cellulose-based products, such as nanocrystalline cellulose (NCC). NCC can be used as a raw material in various industrial sectors, including paper, packaging, food, pharmaceuticals, cosmetics, and electronics industries. The bioprocess technology for producing nanocrystalline cellulose from OPEFB has been successfully developed and is expected to be applied on an industrial scale. Therefore, an economic feasibility analysis is required to evaluate investment viability and the impact of parameter changes on investment using sensitivity analysis for the production of nanocrystalline cellulose from OPEFB with bioprocess technology. Based on the data processing of investment feasibility analysis with assumptions of cost data and other parameters using Internal Rate of Return (IRR), Net Present Value (NPV), and Payback Period (PP), it was found that the industry is feasible and profitable with an IRR of 113.99%, NPV of 763,804,208.84, and a Payback Period of 1 year. Additionally, using sensitivity analysis, it was determined that to maintain investment viability, the raw material price can only increase by a maximum of 35%, the product selling price can only decrease by a maximum of 15%, and production costs can only increase by a maximum of 20%. This research is expected to provide information to stakeholders such as investors, government, and industry regarding the opportunities for developing nanocrystalline cellulose production from OPEFB in Indonesia. Keywords: nanocrystalline cellulose, techno-economic study, oil palm empty fruit bunch, bioprocess technology